Keanekaragaman Gastropoda di Pantai Muko Wujo Kecamatan Larantuka Kabupaten Flores Timur - Malik, Margaretha; Laynurak, Yoseph M.; Semiun, Chatarina Gradict (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Gastropods act as environmental bioindicators because they are sensitive to changes in the aquatic environment. The purpose of this study was to determine the diversity of gastropod species on Muko Wujo Beach. Determination of sampling points using the purposive sampling method. Samples were taken at two different stations based on human activities. The stages in collecting data on gastropod species include observing gastropods found in a 1x1 m plot, counting the number, and then recording it for identification purposes. In addition, environmental parameters, namely temperature and pH, were measured. Data on gastropod species and environmental parameters were then analysed qualitatively and quantitatively. Qualitative analysis was carried out by describing the morphological characteristics of gastropods, and identification was carried out using the help of scientific articles and internet websites. Quantitative analysis was carried out by calculating the diversity index, dominance index and similarity index of gastropod species. The results showed that 29 types of gastropods were found on Muko Beach, Larantuka District, East Flores Regency, which were divided into 14 families and 7 Orders. The diversity index, dominance index, and similarity index of gastropod species on Muko Wujo Beach were classified as moderate.